Islamic Spiritual Deconstruction: Kanjeng Ratu Kidul Myth in Kiai Ibnu Hajar’s View - Suwito, S.; Ulyan, Mohammad; Novianti, Ida; Muflihah, M. (ADDIN, 2020)
This article aims to study and analyze the Islamic spiritual sides of the deconstruction in Kanjeng Ratu Kidul belief from the perspective of Kiai Ibnu Hajar. Kanjeng Ratu Kidul is a very popular myth among people in the southern part of Java Island. Most of them hold annual ceremonies as a way to express their request for having the blessing and being avoided from disasters. The data of this research were collected through in-depth interviews and participatory observations. Derrida’s deconstruction theory was applied to analyze the spirituality aspects. There are three deconstruction processes: (1) logocentric identification; (2) internal contradiction return; (3) difference or building new construction. This research found that Kiai Ibnu Hajar’s deconstruction spirituality was performed in three stages: (1) visual identification stage, which is done through eliciting the discourse of Kanjeng Ratu Kidul by her pictures or photos; (2) returning stage, which is done through mind-verbal activities, i.e. by understanding the nature and existence of human being through religious teachings and informal chats; (3) building new concept, which is actualized through the use of new terms among the members of Jamaah Aolia Panggang Mosque.